The Influence of External Factors on the Success of Coffee Bean Cafes in Medan - Pane, Dewi Nurmasari; El Fikri, Miftah; Ahmad, Rizal; Rahmadani, Rahmadani (International Conference on Sciences Development and Technology, 2023)
The impact of outside factors on the success of the Coffee Bean Café in Medan is the subject of this study. Additionally, information was gathered by sending out questionnaires to thirty respondents. Multiple linear regression is the model utilised, while SPSS version 19 is employed for processing. The analysis using the t test's results reveals that the dependent variable, the success of the Coffee Bean Café (Y), is partially or simultaneously impacted positively and significantly by two independent variables: the family environment (X1), friendship environment (X2), and impulse buying (X3). Price reductions and other unresearched factors account for 25% of the Biji Kopi café's performance in sustaining its company, according to the analysis utilising the coefficient of determination.